2022
DOI: 10.21037/jtd-21-1536
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of echocardiography in evaluating hemodynamics and right ventricular function in patients with chronic thromboembolic pulmonary hypertension after balloon pulmonary angioplasty

Abstract: Background: Patients with inoperable chronic thromboembolic pulmonary hypertension (CTEPH) are eligible for balloon pulmonary angioplasty (BPA). However, the short-term effects of BPA on pulmonary hemodynamics and right ventricular (RV) function in patients with CTEPH have not been elucidated. In the current study, echocardiography was conducted to explore the short-term effects of BPA on inoperable CTEPH patients.Methods: A total of 30 inoperable CTEPH patients who underwent echocardiography before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Finally, we assumed that the RAP estimated by echocardiography from the inferior vena cava diameters and inspiratory collapse was accurate, based on which the consistency of US-PASP and RHC-PASP was analyzed. There may be reputedly imprecise ( 33 , 37 ), but Chen et al ( 38 ) reported that RAMP did not change significantly before and after BPA. However, further study is needed on researching new methods of RAP ultrasound assessment in order to screen suspicious populations reliably.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we assumed that the RAP estimated by echocardiography from the inferior vena cava diameters and inspiratory collapse was accurate, based on which the consistency of US-PASP and RHC-PASP was analyzed. There may be reputedly imprecise ( 33 , 37 ), but Chen et al ( 38 ) reported that RAMP did not change significantly before and after BPA. However, further study is needed on researching new methods of RAP ultrasound assessment in order to screen suspicious populations reliably.…”
Section: Discussionmentioning
confidence: 99%